LECTURERS’ PERCEPTIONS TOWARDS THE IMPLEMENTATION OF HOTS IN ENGLISH LEARNING PROCESS TO THE STUDENTS AT HKBP NOMMENSEN UNIVERSITY PEMATANGSIANTAR - Melda Veby Ristella Munthe; David Togi Hutahean; Tria Joys Siburian (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This research aimed to find out the lecturers’ perceptions towards the implementation of higher order thinking skills (HOTS) in English learning process at HKBP Nommensen University Pematangsiantar. This research used a survey method. The sample of this research consisted of 3 English lecturers at the English Department at HKBP Nommensen University Pematangsiantar. The researcher used a questionnaire as an instrument. Twenty items of closed-ended questionnaires were designed to indicate lecturers’ perceptions. The findings of this research that the respondents were very good perception and were very satisfied towards the implementation of HOTS in English learning process. Therefore, it can be concluded that by applying higher order thinking skills (HOTS) in learning English can make lecturers’ able to prepare teaching materials based on hots. Further research is recommended especially to investigate its effectiveness through experimental research